UJI FISIS BRIKET BIOARANG BERBAHAN BATANG TEH (CAMELLIA SINENSIS) - Abdul Halim Daulay; Masthura Masthura; Heni Puspita Sari (UIN Sumatera Utara Medan, 2022)
Research has been done on the physicl test of charcoal briquettes made from tea stems (Camellia sinensis). This study aims to determine the physical characteristics of the charcoaI briquettes produced. This research is motivated by the increasing demand for human fuel, thus utilizing tea stems as the main ingredient in making briquettes. The sample variations used were tea tree trunk charcoaI and tapioca adhesive as an adhesive with a ratio of 90%:I0%, 80%:20%, 70%:30%, 60%:40%, and 50%:50%. The physical test carried out included water content, density, and calorific value. The results obtained from the physical test of biochar briquettes with the best quality approaching the quality standards of Indonesian briquettes were obtained on sample with a composition (70%:30%) with the value of water content, density, and calorific value, each of which was 5 .70%, 0.55 g/cm3, and (-) 7.62 cal/g.